Moms Are Not OK: COVID-19 and Maternal Mental Health - Davenport, Margie H; Meyer, Sarah; Meah, Victoria L; Strynadka, Morgan C; Khurana, Rshmi (Frontiers in Global Women's Health, 2020)
Depression and anxiety affect one in seven women during the perinatal period, and are associated with increased risk of preterm delivery, reduced mother-infant bonding, and delays in cognitive/emotional development of the infant. With this survey we aimed to rapidly assess the influence of the COVID-19 pandemic and subsequent physical distancing/isolation measures on the mental health and physical activity of pregnant and postpartum women. Between April 14 and May 8, 2020, we recruited women who were pregnant or within the first year after delivery to participate in an online survey. This included questionnaires on self-reported levels of depression/depressive symptoms (Edinburgh Postnatal Depression Survey; EPDS), anxiety (State-Trait Anxiety Inventory; STAI-State), and physical activity. Current and pre-pandemic values were assessed for each. Of 900 eligible women, 520 (58%) were pregnant and 380 (42%) were in the first year after delivery. Sixty-four percent of women reported reduced physical activity with the onset of isolation measures, while 15% increased, and 21% had no change to their physical activity. An EPDS score >13 (indicative of depression) was self-identified in 15% of respondents pre-pandemic and in 40.7% currently (mean ± SD; 7.5 ± 4.9 vs. 11.2 ± 6.3, respectively; < 0.01, moderate effect). Moderate to high anxiety (STAI-state score >40) was identified in 29% of women before the pandemic (mean STAI = 34.5 ± 11.4) vs. 72% of women currently (mean STAI = 48.1 ± 13.6; < 0.01, large effect). However, women engaging in at least 150 min of moderate intensity physical activity (meeting current guidelines) during the pandemic had significantly lower scores for both anxiety and depression than those who did not ( < 0.01, large and small effect, respectively). This rapid response survey identifies a substantial increase in the likelihood of maternal depression and anxiety during the COVID-19 pandemic. This highlights the strong need for heightened assessment and treatment of maternal mental health. However, these data also suggest that physical activity, which has previously been shown to reduce depression and depressive symptoms in pregnancy, may be associated with better mental health during the pandemic.